2016
DOI: 10.1007/jhep08(2016)113
|View full text |Cite
|
Sign up to set email alerts
|

String theory in polar coordinates and the vanishing of the one-loop Rindler entropy

Abstract: Abstract:We analyze the string spectrum of flat space in polar coordinates, following the small curvature limit of the SL(2, R)/U(1) cigar CFT. We first analyze the partition function of the cigar itself, making some clarifications of the structure of the spectrum that have escaped attention up to this point. The superstring spectrum (type 0 and type II) is shown to exhibit an involution symmetry, that survives the small curvature limit. We classify all marginal states in polar coordinates for type II superstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 116 publications
(389 reference statements)
0
12
0
Order By: Relevance
“…To understand the limitations of such a procedure, a concrete avenue would be to further investigate strings on the SL(2, R)/U (1) cigar background, which has Rindler space as a parametric limit (see e.g. [37,[66][67][68][69][70][71][72][73][74]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the limitations of such a procedure, a concrete avenue would be to further investigate strings on the SL(2, R)/U (1) cigar background, which has Rindler space as a parametric limit (see e.g. [37,[66][67][68][69][70][71][72][73][74]).…”
Section: Resultsmentioning
confidence: 99%
“…a trace over a yet-to-be-determined Hilbert space). In recent years, many of these Euclidean calculations have been performed, both in QFT as in string theory [28][29][30][31][32][33][34][35][36][37]. For Maxwell theory, Kabat found a contribution to the partition function due to a coupling of non-scalar fields to the conical singularity introduced in the Euclidean calculation: the contact term.…”
Section: Introductionmentioning
confidence: 99%
“…It would in any case be interesting to understand better the role of edge states within string theory and its relation to the old Susskind-Uglum picture of horizon-piercing strings (see e.g. [62] for a 2d example, and [63][64][65][66] for a variety of results in this direction using Euclidean techniques).…”
Section: Discussionmentioning
confidence: 99%
“…The quantum dimension is the measure of the effective degrees of freedom of a local operator and it is a kind of topological quantity. In various dimensional CFTs, REE has been studied in [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] from various perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The papers [16] [17] [19] [20] mainly concentrated on entanglement entropy in higherdimensional field theory. The authors of [18] have found the REE of local excited states in large central charge 1 + 1 dimensional CFTs from holography.…”
Section: Introductionmentioning
confidence: 99%